The Effect Of Financial Leverage And Operating Leverage On Company Profitability - Qurochman, Arief Nurdiannova; Putra, Arjuna Nur Alfian Syah (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the effect of financial leverage (DFL) and operating leverage (DOL) on company profitability (ROE) both simultaneously and partially in banking sub-sector companies listed on the BEI for the 2020-2022 period. This research was conducted using multiple linear regression analysis. Based on the results of the F test, it is known that DFL and DOL simultaneously influence ROE, this is proven by a significance level that is smaller than 0.05, namely 0.023. Based on the results of the t test, it is known that DFL partially has no effect on ROE, this is proven by a significance level greater than 0.05, namely 0.432. Based on the results of the t test, it is also known that DOL partially has a significant negative effect on ROE, this is proven by a significance level that is smaller than 0.05, namely 0.373. The strength of the relationship between the variables DFL, DOL and ROE is shown by the adjusted coefficient of determination (Adjusted R square) which is only 0.137 or 13.7%.